The Effect of Co2 Concentration and Light Intensity on the Productivity of Scenedesmus sp. In Culture Media - Muh. Dzaky Murtadha; Okik Hendriyanto Cahyonugroho (Green Publisher Indonesia, 2026)
The microalga Scenedesmus sp. is a biological resource with high potential for biomass production and carbon dioxide (CO2) fixation. The productivity of microalgae is highly dependent on the availability of two primary resources: light as the energy source and CO2 as the carbon source. This study aimed to evaluate and determine the optimal combination of CO2 concentration and light intensity that is most effective in maximizing the growth and productivity of Scenedesmus sp. The research utilized a batch cultivation system over a 10-day period in 16 Photobioreactor (FBR) units. A 4×4 factorial experimental design was applied, varying four levels of CO2 concentration (2%, 2.5%, 3%, 3.5%) and four levels of light intensity (3500, 4000, 4500, 5000 Lux). Growth was monitored based on cell density (cells/mL), counted using the Haemacytometer method every two days, and the specific growth rate (μ) was calculated. The results indicated that the growth pattern exhibited a Lag phase (Day 0−2) and an Exponential phase (Day 2−8). The treatment combination of 3% CO2 concentration and 4500 Lux light intensity (FBR 11) consistently yielded the highest cell density, peaking at 1.41×106 cells/mL on Day 8, which also reflected the maximum specific growth rate. Other conditions showed inhibitory effects: the 5000 Lux light intensity caused photoinhibition or damage to the photosynthetic apparatus, while the highest CO2 concentration of 3.5% led to a decline in cell density due to a suspected drop in the medium pH.